Effectiveness of the TM Intranet Website - Nanda Kumara Panian, Seenivasagam (2008)
The purpose of this research is to study the effectiveness of the TM online information website in achieving the desired information dissemination in order for the staffs to acquire the necessary knowledge. The aims are to identify the effectiveness of the TM Intranet website and to provide recommendations for the future improvement of the system. In this study, staffs using the TM Intranet environment daily at their work premises were surveyed through online survey to evaluate the intranet system. About 50 staffs were targeted to participate and the respondents were only 42. Results showed that there are three main factors that influence the effectiveness of the TM Intranet website in relation to their daily work. These factors are staffs’ behavior and attitude, technology and system, and interactive applications. The paper discusses these factors in detail with an emphasis on the role of the TM Intranet website in information and knowledge dissemination for the staff in their daily work environment.